A Survey for Escherichia coli Virulence Factors in Asymptomatic Free-Ranging Parrots. (10th July 2012) - Becker Saidenberg, André; Robaldo Guedes, Neiva Maria; Fernandes Seixas, Gláucia Helena; da Costa Allgayer, Mariangela; Pacífico de Assis, Erica; Fabio Silveira, Luis; Anne Melville, Priscilla; Benites, Nilson Roberti
Abstract : Parrots in captivity are frequently affected by Escherichia coli ( E. coli ) infections. The objective of this study was to collect information on the carrier state for E. coli pathotypes in asymptomatic free-ranging parrots. Cloacal swabs were collected from nestlings of Hyacinth, Lear's macaws and Blue-fronted Amazon parrots and tested by polymerase chain reaction (PCR) for virulence factors commonly found in enteropathogenic, avian pathogenic, and uropathogenic E. coli strains. In total, 44 samples were cultured and E. coli isolates were yielded, from which DNA was extracted and processed by PCR. Genes commonly found in APEC isolates from Blue-fronted Amazon parrots and Hyacinth macaws were expressed in 14 of these 44 samples. One atypical EPEC isolate was obtained from a sample from Lear's macaw. The most commonly found gene was the increased serum survival ( iss ) gene. This is the first report, that describes such pathotypes in asymptomatic free-living parrots. The findings of this study suggest the presence of a stable host/parasite relationship at the time of the sampling brings a new understanding to the role that E. coli plays in captive and wild parrots. Such information can be used to improve husbandry protocols as well as help conservation efforts of free-living populations.